A detailed study on simultaneous heat and mass transfer in an in-tube vertical falling film absorber. (August 2017) - Aminyavari, Mehdi; Aprile, Marcello; Toppi, Tommaso; Garone, Silvia; Motta, Mario
Highlights: A lumped element model of a vertical in-tube falling film absorber was built. Tests have been performed on an existing Heat Transformer for validation. The model has been validated by the experimental data obtained from the tests. Sensitivity of the model with respect to the inlet condition has been evaluated. Insight is given to simultaneous heat and mass transfer along the falling film. Abstract: In the present study, a numerical model of a vertical in-tube falling film absorption heat exchanger utilizing NH 3 − H 2 O pair as working fluid is developed. At first, the results of the simulations are validated with experimental data obtained from the absorber of an Absorption Heat Transformer (AHT). Then, in order to comprehend the effect of measurements errors on the results of the model, the sensitivity of the model with respect to the measured inlet conditions is investigated. Furthermore, simultaneous heat and mass transfer along the interface throughout the pipes length is studied. Results indicate that the main resistances for heat and mass transfer are the ones between gas and interface. It has been also found that the majority of the gas gets absorbed by the film in the top segments of the pipes since the driving forces along the interface are higher in these segments.